FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI - Ganison Ganison; Jamaludin Iskak (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of Profitability, Leverage, Liquidity, Firm Size, and Firm Growth on Dividend Policy in property companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Sample was selected using purposive samplingmethod and the valid data was 11 companies. The data processing technique uses multiple regression analysis what helped by IBM SPSS program (Statistical Product and Service Solution) for Windows released 24 and Microsoft Excel 2016. The results of this studyindicate that the results of this study indicate that Profitabilty, and Liquidity have a significant and positive influence on dividends. Policy, then Firm Growth has a significant and negative effect on Dividend Policy, while Leverage and Firm Size do not have a significant effect on Dividend Policy. The implication of this research is the need to increase the role of company management to determine Dividend Policy which can provide the return (return) that investors want and also improve company performance.